Archipelagic Eco-Futures: Eco-anxiety dan Harapan Ekologis dalam Fiksi Iklim Indonesia dan Filipina - Fredy Yunanto; Evha Nazalatus Sa’adiyah Sy (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2025)
This article analyses the representation of eco-anxiety and narratives of ecological hope in two contemporary Southeast Asian Climate fiction texts: The Fires of Tanam Alkin (2023) by Sadie Noni from Indonesia and Sigwa: Climate fiction Anthology from the Philippines (2020) edited by Paolo Enrico Melendez and Kristine Ong Muslim. This research stems from a gap in studies that have thus far focused on Climate fiction works from the Global North, while literature from Southeast Asia has rarely been studied despite the region being one of the most vulnerable to the climate crisis. Using an affective ecocritical approach and comparative archipelagic literature, this study examines how ecological trauma and eco-anxiety are mediated by the colonial, geographical, and cultural contexts of the archipelago. The analysis shows that both texts present eco-anxiety not merely as a universal fear, but as an affective-political experience influenced by colonial memory, spiritual relations with nature, and structural ecological injustice. The Fires of Tanam Alkin emphasises the ecological trauma of indigenous communities due to industrial deforestation, while Sigwa shows the plurality of voices of Filipino coastal communities facing sea flooding, ecological migration, and loss of spiritual space. The main contribution of this research is the proposal of the concept of archipelagic eco-futures, namely a framework for reading Southeast Asian Climate fiction as a space for articulating trauma and imagining an ecological future. This article demonstrates that Climate fiction can expand ecological literacy in Southeast Asia, not only as a reflection of crisis, but also as a medium for education, cultural policy, and public literacy practices to build intergenerational ecological awareness. Thus, this research opens up a new direction for global ecocritical studies and affirms the role of literature as an imaginative laboratory for an equitable and sustainable ecological future.